Augmented reality and the customer journey: An exploratory study. Issue 4 (November 2021) - Romano, Beatrice; Sands, Sean; Pallant, Jason I.
Many firms, including Amazon and IKEA, utilise augmented reality (AR) technology to enhance the consumer experience. In the retail industry, AR is gaining increasing traction as a means of improving the customer experience overall. In this research, we conduct an exploratory analysis to determine whether AR contributes positively or otherwise to customer experience. By means of semi-structured interviews, we identify seven core themes pertinent to the customer journey. Findings suggest that, prior to purchase, AR can broaden consumers' product consideration set, while narrowing the choice set. Moreover, we find evidence that AR can lessen brand value, thereby giving emerging brands the opportunity to connect with consumers. Findings indicate that, at the point of purchase, AR can help with product curation and drive hedonic value through playfulness. Finally, at the post-purchase stage, findings show that AR can influence consumer choice confidence, and can also amplify cognitive dissonance. From these themes, we draw implications for theory as well as managerial implications in terms of balancing the potential promises and perils of AR as an innovation technology.